IMPACT DE L’IRRIGATION AVEC DES EAUX CHARGEES EN MATIERES EN SUSPENSION SUR LA PERMEABILITE DU SOL CAS DE LA PLAINE DE L’HABRA (ALGERIE) - Mohamed, Gliz; Djamel, Anteur; Mohammed, Makhlouf (European Scientific Journal, ESJ, 2014)
Water from the Fergoug dam is intended to irrigate farmland in the plains of Habra; however this water is loaded with suspended solids, which resulted in adverse effects on soils, crop yields and environment. A work at the laboratory which consists in introducing different concentrations of suspended matter, inspired by the dam released on the said land, was used to identify the relationship between the load of suspended solids in the irrigation water, the variation permeability and the number of corresponding irrigations. The got results seem to have an interest practises then that make it possible to the decision makers to see the danger which presents this load contained in water of irrigation on becoming it of these agricultural lands.